PENGEMBANGAN MODUL MATEMATIKA BERBASIS PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN LITERASI MATEMATIS KELAS VII - Muslim, Muhammad Fachri (Departemen Matematika, 2023)
Indonesia in participating in assessing student’s literacy and numeracy abilities obtained unsatisfactory results. The level of literacy ability of students is still said to be low. So that the PISA report is used as a basis for improving the curriculum in Indonesia, where (Pratiwi (2019:51)) reveals that the PISA program greatly impacts changes in the Indonesian curriculum. Therefore, theacers are required to be creative in announcing learning that involves the active participation of students. In general, the teaching materials used by teachers and students in learning are in the form of worksheets that were not designed by the teacher himself. The problem-based learning module discusses learning material based on objects that are presented contextually. The type of research used is research and development (R&D). Where the aim is that from this research a module can e developed that can improve student’s literacy skills. The validity of the learning module gets a value of 83,34%, which concludes that the module is valid from all aspects of validity that has been compiled so that it is good to use or try out on students. Then, after being tried out this module was assessed for practicality with a value 88,06% so it was also concluded that this module was very practical and feasible to use. So, in the end this module as a vaid and practical module.Keywrods –Module, PBL, Practicality, Validity